Synthesis and characterization of novel post-chain extension flame retardant waterborne polyurethane. Issue 118 (16th November 2015) - Wu, Gang; Li, Jinqing; Chai, Chunpeng; Ge, Zhen; Lin, Jialun; Luo, Yunjun
Abstract : Flame-retardant waterborne polyurethanes with a phosphorus-containing flame retardant diamine (AWPUs) were synthesized and characterized by the method of post-chain extension technology. Abstract : A series of novel flame-retardant waterborne polyurethanes with a phosphorus-containing flame retardant diamine (AWPUs) were synthesized by the method of post-chain extension and the effect of the chain extender on the properties of AWPU dispersions were investigated. The results revealed that the chain extension increased the molecular weight and the molecular weight distribution. The emulsions AWPUs still maintained their stability and particle sizes increased after post-chain extension. AWPUs with a post-chain extension of bis(4-aminophenoxy)phenyl phosphine oxide were successfully prepared and characterized using FTIR and NMR analysis. The hydrogen bonds in hard segments and the phase separation between hard segments and soft segments were enhanced. Moreover, the phosphorus-containing chain extender improved the tensile strength but decreased the elongation at break. With the increase of chain extension ratio, the glass transition temperature for hard segments showed an increasing trend but the glass transition temperature for soft segments showed a decreasing trend. The phosphorus-containing chain extender reduced the thermal stability of AWPUs and favored the degradation of AWPUs. Finally, the flame retardancy was improved with the flame-retardant extender added.